Instagram Posts Related to Backwoods Cigarillo Blunts: Content Analysis - Kim, Stephanie; Mourali, Alia; Allem, Jon-Patrick; Unger, Jennifer B; Boley Cruz, Tess; Smiley, Sabrina L (JMIR Publications, 2021)
BackgroundInstagram, one of the most popular social media platforms among youth, offers a unique opportunity to examine blunts-partially or fully hollowed-out large cigars, little cigars, and cigarillos that are filled with marijuana. Cigarillo brands like Backwoods (Imperial Tobacco Group Brands LLC) have product features that facilitate blunt making, including a variety of brand-specific flavors that enhance the smoking experience (eg, honey, dark stout). Backwoods has an active online presence with a user-friendly website. ObjectiveThis study examined the extent to which Backwoods cigarillo-related posts on Instagram showed blunt making. Instagram offers a unique opportunity to examine blunt making as Instagram accounts will contain images reflective of behavior occurring without the prime of a researcher. MethodsData consisted of publicly available Instagram posts with the hashtag #backwoods collected from August 30 to September 12, 2018. Inclusion criteria for this study included an Instagram post with the hashtag "#backwoods". Rules were established to content analyze posts. Categories included Type of post (ie, photo, video, or both); Blunt-related hashtags (ie, the corresponding post caption contained one or more hashtags like #blunts, #cannabis, and #weed that were identified in previous social media research); Rolling blunts (ie, the post contained an image of one or more individuals rolling a Backwoods cigarillo visibly containing marijuana); and Smoking blunts (ie, the post contained an image of one or more individuals blowing smoke or holding a lit blunt). We coded images for Product flavor reference, where a code of 1 showed a Backwoods cigarillo pack with a brand-specific flavor (eg, honey, dark stout, Russian crème) visible in the blunt-related image, and a code of 0 indicated that it was not visible anywhere in the image. ResultsAmong all posts (N=1206), 871 (72.2%) were coded as Blunt-related hashtags. A total of 125 (10.4%) images were coded as Smoking blunts, and 25 (2.1%) were coded as Rolling blunts (ie, Backwoods cigarillo explicitly used to roll blunts). Among blunt images, 434 of 836 (51.9%) were coded as Product flavor (ie, a Backwoods pack with a brand-specific flavor was visible). ConclusionsMost Backwoods cigarillo-related Instagram images were blunt-related, and these blunt-related images showed Backwoods packages indicating flavor preference. Continued monitoring and surveillance of blunt-related posts on Instagram is needed to inform policies and interventions that reduce the risk that youth may experiment with blunts. Specific policies could include restrictions on product features (eg, flavors, perforated lines, attractive resealable foil pouches, sale as singles) that facilitate blunt making.